2018
DOI: 10.1093/ehjci/jey188
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic reference ranges for normal non-invasive myocardial work indices: results from the EACVI NORRE study

Abstract: To obtain the normal ranges for 2D echocardiographic (2DE) indices of myocardial work (MW) from a large group of healthy volunteers over a wide range of ages and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
215
7
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(272 citation statements)
references
References 28 publications
18
215
7
13
Order By: Relevance
“…In a large multicenter study, the median GWI of healthy subjects was 1896 ± 308 mm Hg%. 15 Other studies showed significantly lower GWI values of 1078 ± 506 mm Hg% in patients with dilated cardiomyopathy. 10 We focused on patients with severe heart failure in a center specialized in heart transplantation and assist device implantation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a large multicenter study, the median GWI of healthy subjects was 1896 ± 308 mm Hg%. 15 Other studies showed significantly lower GWI values of 1078 ± 506 mm Hg% in patients with dilated cardiomyopathy. 10 We focused on patients with severe heart failure in a center specialized in heart transplantation and assist device implantation.…”
Section: Discussionmentioning
confidence: 91%
“…Normal values have recently been published and work indices have been measured in patients with heart failure . This work describes for the first time the relation between classic prognostic parameters and work indices in a heart failure population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results illustrated that subclinical changes in LV systolic function have occurred in athletes and MW indexes were more sensitive to provide early diagnosis value for LV performance among athletes. 24 According to the ROC analysis about LVMW parameters, GWE (AUC = 0.733) was considered of being the best predictor of LV systolic function in athletes and superior to GLS (AUC = 0.627) which was principally limited by the defect of being load-dependent and might lead to errors in judging LV performance. 25 Limitations Several limitations to this study need to be acknowledged as follows: (i) The sample scale was small.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased afterload may cause lower LV strain, leading to misjudgment of the real LV systolic function [10]. Myocardial work (MW), which is derived from 2D-STI, combines the LV pressure (derived from the systolic pressure in the brachial artery) measured using a noninvasive method and the longitudinal strain data for the LV myocardium to establish the LV pressure-strain loops (PSL) [11]. This approach can be used to examine the dynamic changes in LV MW when LV becomes deformed due to overcoming the afterload.…”
Section: Introductionmentioning
confidence: 99%